2019
DOI: 10.3390/cancers11121920
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Tumour Microenvironment: Challenges and Future Perspectives for Anticancer Plasma Treatments

Abstract: Tumours are complex systems formed by cellular (malignant, immune, and endothelial cells, fibroblasts) and acellular components (extracellular matrix (ECM) constituents and secreted factors). A close interplay between these factors, collectively called the tumour microenvironment, is required to respond appropriately to external cues and to determine the treatment outcome. Cold plasma (here referred as ‘plasma’) is an emerging anticancer technology that generates a unique cocktail of reactive oxygen and nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 307 publications
(334 reference statements)
0
56
0
1
Order By: Relevance
“…Effects of CAP have been observed on different parts of the TME, which is composed of malignant cells, immune cells, endothelial cells, fibroblasts, tumor vasculature and the extracellular matrix, which are in constant communication with each other. In addition to the various cell types, the TME consists of collagen, elastin, fibronectin, glycoproteins, and proteoglycan [92]. It has been observed that prolonged treatment with CAP inhibits cell viability and collagen production of murine fibroblasts [93].…”
Section: Cap Interaction With the Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of CAP have been observed on different parts of the TME, which is composed of malignant cells, immune cells, endothelial cells, fibroblasts, tumor vasculature and the extracellular matrix, which are in constant communication with each other. In addition to the various cell types, the TME consists of collagen, elastin, fibronectin, glycoproteins, and proteoglycan [92]. It has been observed that prolonged treatment with CAP inhibits cell viability and collagen production of murine fibroblasts [93].…”
Section: Cap Interaction With the Tumor Microenvironmentmentioning
confidence: 99%
“…It has also been shown that calcium ions can be transported from apoptotic to non-apoptotic neighbour cells via gap junctions, which also explains the widespread effect of plasma [107]. A comprehensive review on CAP effects regarding numerous other parts of the TME was provided by Privat-Maldonado et al [92].…”
Section: Cap Interaction With the Tumor Microenvironmentmentioning
confidence: 99%
“…It is well known that the tumor microenvironment (TME) contributes to cancer development and promotes angiogenesis, invasion, metastasis, and chronic inflammation [19]. The possible role of TME in response to chemotherapy [20] or antiangiogenic therapy [21] has been addressed recently.…”
Section: Introductionmentioning
confidence: 99%
“…The possible role of TME in response to chemotherapy [20] or antiangiogenic therapy [21] has been addressed recently. In healthy tissues the wound healing process is promoted by the activation, migration, and proliferation of fibroblasts, whereas cancer-associated fibroblasts play a role in tumor growth and therefore are crucial for disease progression [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue on “Plasma in Cancer Treatment” brings together 16 original research papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and two insightful reviews [ 24 , 25 ]. The papers published in the Special Issue provide valuable information regarding the efficacy of CAP against osteosarcoma, glioblastoma, cholangiocarcinoma, melanoma, pancreatic, ovarian, breast, cervical and colorectal cancer.…”
mentioning
confidence: 99%